2010
DOI: 10.1007/s11240-010-9831-4
|View full text |Cite
|
Sign up to set email alerts
|

Haploids and doubled haploids in Brassica spp. for genetic and genomic research

Abstract: The availability of a highly efficient and reliable microspore culture protocol for many Brassica species makes this system useful for studying basic and applied research questions. Microspores and microspore-derived embryos are ideal targets for modification by mutagenesis and transformation. Regenerated doubled haploid plants are widely used in breeding programs and in genetic studies. Furthermore, the Brassica microspore culture system allows the identification of genomic regions and genes involved in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(63 citation statements)
references
References 82 publications
0
63
0
Order By: Relevance
“…Variation and mutagenesis of plantlets were also appreciated by geneticists and breeders (Dunwell 2010;Ferrie and Möllers 2010). We obtained several plantlets that were sensitive to bolt even without any cold treatment in culture or soon after transplanting (Fig.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Variation and mutagenesis of plantlets were also appreciated by geneticists and breeders (Dunwell 2010;Ferrie and Möllers 2010). We obtained several plantlets that were sensitive to bolt even without any cold treatment in culture or soon after transplanting (Fig.…”
Section: Discussionmentioning
confidence: 91%
“…Selection and production of inbred lines is time consuming and difficult to achieve. Even with 6 years of self-pollination by conventional breeding methods, only about 98 % homozygosity could be achieved (Germanà 2006;Ferrie and Möllers 2010). Moreover, the vigor of early-generation carrot inbred lines selected from open-pollinated cultivars decreases dramatically due to inbreeding depression (Peterson and Simon 1986).…”
Section: Introductionmentioning
confidence: 99%
“…Traits are fixed and homozygous true breeding lines are produced within one generation, which can help reduce the time needed to develop new varieties (Thomas et al 2003;Ferrie and Caswell 2011;Ferrie and Möllers 2011). For the same reasons, in vitro microspore culture has become an important tool for mutagenesis (Barro et al 2001(Barro et al , 2002Sonntag and Rudloff 2004;Liu et al 2005;Ferrie et al 2008) and in vitro selection (Albrecht et al 1995;Möllers et al 2000;Liu et al 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In rapeseed, F 1 derived segregating DH populations have been extensively used for map construction and the genetic analysis of important traits (Ferreira et al 1994;Parkin et al 1995;Sharpe et al 1995;Uzunova et al 1995;Zhao et al 2005;Delourme et al 2006;Qiu et al 2006;Radoev et al 2008). In these mapping studies distorted marker segregations have been observed regularly (summarized in Ferrie and Möllers 2011). This is often explained by the assumption that the selection of favourable alleles at loci controlling microspore embryogenesis leads to skewed segregations at linked marker loci (Foisset et al 1993;Cloutier et al 1995;Foisset and Delourme 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The biotechnology of producing pure breeding lines, the doubled haploids, via anthers and isolated microspore cultures is recently widely applicable in genetic studies and breeding cole crops (1)(2)(3). Due to this approach, the in vitro generated plants have different ploidy, and, together with doubled haploids, also haploid, tetraploid and mixoploid forms can occur (4).…”
mentioning
confidence: 99%